Iron metabolism in copper-deficient swine - Lee, G. Richard; Nacht, Sergio; Lukens, John N.; Cartwright, G. E. (The Journal of Clinical Investigation, 1968)
The way in which iron is handled by the duodenal mucosa, the reticuloendothelial system, the hepatic parenchymal cell, and the normoblast was investigated in copper-deficient swine. Copper-deficient swine failed to absorb dietary iron at the normal rate. Increased amounts of stainable iron were observed in fixed sections of duodenum from such animals. When 59iron was administered orally, the mucosa of copper-deficient animals extracted iron from the duodenal lumen at the normal rate, but the subsequent transfer to plasma was impaired. When intramuscular iron supplements were given to copper-deficient pigs, increased amounts of iron were found in the reticuloendothelial system, the hepatic parenchymal cells, and in normoblasts (sideroblasts). Hypoferremia was observed in the early stages of copper deficiency, even though iron stores were normal or increased. When red cells that were damaged by prolonged storage were administered, the reticuloendothelial system failed to extract and transfer the erythrocyte iron to the plasma at the normal rate. Administration of copper to copper-deficient animals with normal iron stores resulted in a prompt increase in the plasma iron. The observed abnormalities in iron metabolism are best explained by an impaired ability of the duodenal mucosa, the reticuloendothelial system, and the hepatic parenchymal cell to release iron to the plasma. It is suggested that copper is essential to the normal release of iron from these tissues. This concept is compatible with the suggestion made by others that the transfer of iron from tissues to plasma requires the enzymatic oxidation of ferrous iron, and that the plasma copper protein, ceruloplasmin, is the enzyme (ferroxidase) which catalyzes the reaction. Because excessive amounts of iron were found in normoblasts, it is suggested that an additional defect in iron metabolism affects these cells and plays a major role in the development of anemia. As a result of the proposed defect, iron cannot be incorporated into hemoglobin and, instead, accumulates as nonhemoglobin iron. Images